"Gilbertville, " "Ilitchville, " and the Redevelopment of Detroit. (February 2021) - Biles, Roger; Rose, Mark
First, we examine Businessmen Daniel B. "Dan" Gilbert and Michael "Mike" Ilitch's multibillion-dollar investments in Detroit's office buildings and entertainment venues. Next, we set their entrepreneurial activities against the city and region's historical political economy extending back to the early 1900s. Third and finally, we determine that Gilbert and Ilitch's plans for entertainment and commercial development took precedence over planners and their grand plans for citywide and region-wide redevelopment.